Reputation and the Market for Distressed Firm Debt - Noe, Thomas H.; Rebello, Michael J. (Journal of Financial and Quantitative Analysis, 2003)
Our analysis explains how vulture investors (vultures) can maintain and exploit their rep- utations for toughness. Vultures leverage their reputations to extract concessions from stockholders in debt restructurings. To profit from these concessions, vultures must first acquire debt from incumbent bondholders. Buying only the tranches most likely to render them marginal creditors maximizes vulture leverage in debt-purchase negotiations. Vulture profits are proportional to the degree of uncertainty regarding the identity of the marginal debt class